Unusual Presentation of Peripheral Primitive Neuroectodermal Tumor: A Rare Case Report - Singh, Kanika; Raychaudhuri, Sujata; Chauhan, Varsha; Bajaj, Akanksha; Menia, Reetika (International Journal of Human and Health Sciences (IJHHS), 2021)
A primitive neuroectodermal tumor (PNET) is a rare entity occurring most commonly in the 2nd and 3rd decade and is very rare in patients over 40 years of age. PNET is a round cell malignancy of presumably primitive neuroectodermal tissue or migratory neural crest cells arising from soft tissue or bone. PNET occurring outside the central nervous system is called peripheral PNET (p PNET) and most commonly involves the trunk and extremities Here we present a case of PNET diagnosed in an elderly male who presented with a soft tissue mass in the gluteal region. The histopathology with ancillary techniques including immunohistochemistry and molecular studies helped in establishing the diagnosis of PNET. They are characterized by translocation leading to the fusion of Ewing’s Sarcoma (EWS) gene on 22q12 with any of the member of the ETS (E 26 transformation specific or E -twenty – six) family of transcription factors with the most frequent being t (11;22) (q24;12). Intensive multiagent chemotherapy is the mainstay of treatment as it has great potential for metastatic spread. The prognosis of adults with Ewing’s sarcoma (ES)/PNET is not well known, however, some reports suggested that adults with ES/PNET have a poorer prognosis than children. Cytology is the first line of diagnosis for RCT. However, the type-specific diagnosis or final diagnosis of p PNET is based on histopathology aided with IHC and other ancillary techniques. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 358-361